Participatory Silage Making and Hay and Silage Mixed Feeding Technology for Winter Feeding to Goats in Jumla, Nepal (Nepalese Veterinary Journal, 2018)
This action research was carried out to demonstrate the method of silage making and its feeding, mixed with chopped hay to goats during feed scarcity periods as coping strategy for winter days in Jumla. Nine farmers took part in on-farm silage production and feeding trial. A total of 29 kids and 16 does as treatment group and 12 kids and 19 does of the similar age group and status as control were selected to compare the body weight gain. The normal practice of feeding was 3-4 hours of grazing daily, occasionally combined with tree fodder (Quercus sp.) in communal pastureland and offering hay for snowfall days in pens. In addition to this, treatment groups were supplemented with mixed silage and chopped hay at the rate of 2% of body weight on dry matter basis, half each from the silage and hay. The mixture was given daily early in the morning for 45 days from 25th of December to 10th of February, when the average minimum temperature dropped from -2.4 to -5.4° C. Goats consumed about 95% of the offered amount of silage whereas chopped hay was rejected by about 90%. The result showed that kids gained 0.49 kg with average daily gain of 10.88 g and does gained 2.44 kg with an average daily gain of 54.22 g for the treatment group. The difference between the initial and final body weight was positive for treatment group whereas it was negative for the control. Male kids grew faster by 8.6%, female kids by 6.7% and does by 12.6% for silage supplemented group compared to control. It indicated that proper fermented maize fodder silage can be obtained from pits prepared before winter and loss in body weight can be prevented by the supplementation of silage during cold days in high mountains when there is scarce of green forages.